2015
DOI: 10.1155/2015/532481
|View full text |Cite
|
Sign up to set email alerts
|

Resilience at the Transition to Agriculture: The Long-Term Landscape and Resource Development at the Aceramic Neolithic Tell Site of Chogha Golan (Iran)

Abstract: The evidence for the slow development from gathering and cultivation of wild species to the use of domesticates in the Near East, deriving from a number of Epipalaeolithic and aceramic Neolithic sites with short occupational stratigraphies, cannot explain the reasons for the protracted development of agriculture in the Fertile Crescent. The botanical and faunal remains from the long stratigraphic sequence of Chogha Golan, indicate local changes in environmental conditions and subsistence practices that charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 68 publications
2
24
0
Order By: Relevance
“…From the case studies examined in the section 'Environment and fire ecology and fuel selection in the Central Zagros', there is some evidence for local and regional variation in environment and fire resources and fuel selection in the Zagros. This supports wider theories firstly, on the interconnectedness of the environmental, economic, technological and social considerations influencing fuel selection examined in the section 'Interdisciplinary theory in fire ecology and fuel selection' (Charles et al, 2014;Marchant and Lane, 2014;Sillar and Tite, 2000), and secondly, on local and regional variation in environment and ecological strategies in pathways to sedentism and early agriculture, and of multiple centres of innovation, within inter-connected networks across Southwest Asia in the Early Holocene (Riehl et al, 2015;Willcox, 2005;Zeder, 2009). In the Zagros case studies, significant linkages have been identified between transitions to early sedentism and plant and animal management and domestication and the availability and choices in selection of fuel.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…From the case studies examined in the section 'Environment and fire ecology and fuel selection in the Central Zagros', there is some evidence for local and regional variation in environment and fire resources and fuel selection in the Zagros. This supports wider theories firstly, on the interconnectedness of the environmental, economic, technological and social considerations influencing fuel selection examined in the section 'Interdisciplinary theory in fire ecology and fuel selection' (Charles et al, 2014;Marchant and Lane, 2014;Sillar and Tite, 2000), and secondly, on local and regional variation in environment and ecological strategies in pathways to sedentism and early agriculture, and of multiple centres of innovation, within inter-connected networks across Southwest Asia in the Early Holocene (Riehl et al, 2015;Willcox, 2005;Zeder, 2009). In the Zagros case studies, significant linkages have been identified between transitions to early sedentism and plant and animal management and domestication and the availability and choices in selection of fuel.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies of early agricultural fire ecology and use have focused largely on Turkey and the Levant (Asouti and Austin, 2005;Gur-Arieh et al, 2014;Mentzer, 2014;Roberts, 2002). This paper examines new and existing data from the eastern Fertile Crescent to study the impact and use of fire in early agricultural environments and communities in another key heartland of change, as recent studies suggest that there was considerable regional and local variation in environment and ecological strategies and multiple centres of domestication (Riehl et al, 2015;Willcox, 2005;Zeder, 2009). It focuses in particular on the Central Zagros in Iraq and Iran to study highland-lowland variation in humanfire relations, with selective comparison with examples from Anatolia that have been examined in similar ways (Asouti and Austin, 2005;Asouti and Kabukcu, 2014;W Matthews, 2005aW Matthews, , 2005bW Matthews, , 2010Mentzer, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Riehl et al presented first results on the palaeoecology of Chogha Golan [ 64 ]. According to the anthracological analysis, the nearby semiarid Pistacia - Amygdalus woodland steppe and the riparian vegetation were exploited for wood resources.…”
Section: Methodsmentioning
confidence: 99%
“…A considerable increase in small-seeded grasses between AH V and III may indicate a shift in resource availability with a possible contribution of climatic fluctuations. The abundant wild barley grain and chaff remains, combined with temporal grain size increases paralleled by high δ13C values indicative of enhanced growing conditions, may reflect management practices during this phase [ 64 ] and we do not rule out this possibility for the equally abundant Aegilops sp. remains [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation